Naujos kvalifikacijos bibliotekininkų rengimo pagrindai (rusų k.) - Prokopčik, Marija (Knygotyra, 1988)
The application of computers and the changing technology of library work reveal new professional demands for librarians, which necessitate changes in the education for librarianship and information work. The article addresses the theoretical questions of the content of education for the specialty "Librarianship and Bibliography" at the University of Vilnius. The offered complex of subjects is analyzed, and the main tendencies in the development of the curriculum are traced. The modification of library education is based on a new learning plan, which allows for the integration of individual subjects into blocks. This approach enables the selection of a central subject that forms the foundation of the new educational system and integrates separate blocks into one complex. In our opinion, this central subject is "Information Retrieval Systems." The main reasons for this choice, as well as the practical and theoretical advantages, are examined and justified.